Assessment of exposure to pesticide mixtures in five European countries by a harmonized urinary suspect screening approach - Ottenbros, Ilse; Lebret, Erik; Huber, Carolin; Lommen, Arjen; Antignac, Jean-Philippe; Čupr, Pavel; Šulc, Libor; Mikeš, Ondřej; Szigeti, Tamás; Középesy, Szilvia; Martinsone, Inese; Martinsone, Zanna; et al. (International journal of hygiene and environmental health, 2023)
Humans are exposed to a mixture of pesticides through diet as well as through the environment. We conducted a suspect-screening based study to describe the probability of (concomitant) exposure to a set of pesticide profiles in five European countries (Latvia, Hungary, Czech Republic, Spain and the Netherlands). We explored whether living in an agricultural area (compared to living in a peri-urban area), being a a child (compared to being an adult), and the season in which the urine sample was collected had an impact on the probability of detection of pesticides (-metabolites). In total 2088 urine samples were collected from 1050 participants (525 parent-child pairs) and analyzed through harmonized suspect screening by five different laboratories. Fourty pesticide biomarkers (either pesticide metabolites or the parent pesticides as such) relating to 29 pesticides were identified at high levels of confidence in samples across all study sites. Most frequently detected were biomarkers related to the parent pesticides acetamiprid and chlorpropham. Other biomarkers with high detection rates in at least four countries related to the parent pesticides boscalid, fludioxonil, pirimiphos-methyl, pyrimethanil, clothianidin, fluazifop and propamocarb. In 84% of the samples at least two different pesticides were detected. The median number of detected pesticides in the urine samples was 3, and the maximum was 13 pesticides detected in a single sample. The most frequently co-occurring substances were acetamiprid with chlorpropham (in 62 urine samples), and acetamiprid with tebuconazole (30 samples). Some variation in the probability of detection of pesticides (-metabolites) was observed with living in an agricultural area or season of urine sampling, though no consistent patterns were observed. We did observe differences in the probability of detection of a pesticide (metabolite) among children compared to adults, suggesting a different exposure and/or elimination patterns between adults and children. This survey demonstrates the feasibility of conducting a harmonized pan-European sample collection, combined with suspect screening to provide insight in the presence of exposure to pesticide mixtures in the European population, including agricultural areas. Future improvements could come from improved (harmonized) quantification of pesticide levels.
Keywords: Pesticide exposure; pesticidy; Humans; Chlorpropham; Evropa; Agriculture; vystavení vlivu životního prostředí; dospělí; lidé; Biomarkers; Europe; Pesticides; Adult; biologické markery; zemědělství; Co-occurrence; Suspect screening; chlorprofam; Environmental Exposure; Mixtures; Correlation patterns; HBM4EU